ISLAM KOSMOPOLITAN DALAM PEMIKIRAN ABDURRAHMAN WAHID: RELEVANSI BAGI PLURALISME INDONESIA - M. Anang Sholikhudin; Nela Cahya Anggraini; Nia Mamlu'ul Hikmah (Journal Multicultural of Islamic Education, 2025)
This study investigates Abdurrahman Wahid’s concept of cosmopolitan Islam, which serves as a critical framework for developing an inclusive, democratic, and humanistic Islamic discourse in Indonesia. The core issue addressed in this research is the tension between exclusive religious interpretations and the pluralistic vision promoted by Wahid. The purpose of this study is to explain the theoretical construction of cosmopolitan Islam in Wahid’s thought and to analyze its relevance to contemporary socio-religious challenges. This research employs a qualitative library research approach by examining Wahid’s writings, scholarly literature, and previous studies related to pluralism, religious moderation, and multiculturalism. The findings reveal that Wahid’s cosmopolitanism is grounded in universal human values, cultural openness, and interreligious dialogue. His ideas are reflected not only in theoretical discussions but also in practical actions, including the defense of minority rights, the promotion of democratic principles, and the recognition of local cultures as legitimate expressions of Islamic identity. The study concludes that Wahid’s cosmopolitan Islam remains highly relevant for strengthening religious moderation and countering intolerance in modern Indonesia.